The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1007/s10531-012-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and community structure in sal (Shorea robusta) forests of two different rainfall regimes in West Bengal, India

Abstract: Knowledge on the structure and composition of the plant communities has enormous significance in conservation and management of forests. The present study aimed to assess the community attributes, viz., structure, composition and diversity in the moist and dry sal (Shorea robusta) forests in the West Bengal province of India and compare them with the other sal forests of India. The phytosociological data from these forests were quantitatively analysed to work out the species richness, diversity, evenness, domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 23 publications
5
21
3
Order By: Relevance
“…A study from foothills of Darjeeling Himalaya showed that the diversity of tree species is much higher in sal forests than previously hypothesized (Shankar 2001). Subsequent studies from the same region confirmed the trend (Kushwaha and Nandy 2012).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…A study from foothills of Darjeeling Himalaya showed that the diversity of tree species is much higher in sal forests than previously hypothesized (Shankar 2001). Subsequent studies from the same region confirmed the trend (Kushwaha and Nandy 2012).…”
Section: Introductionmentioning
confidence: 67%
“…However, a case of high tree diversity in a sal forest was reported from Mahananda wildlife sanctuary in foothills of eastern Himalaya in the beginning of this century (Shankar 2001). Further investigation spanning larger geographical area of eastern Himalayan terai (including Darjeeling, Jalpaiguri and Coochbehar) endorsed that sal forests of this region harbour high levels of woody species diversity (Kushwaha and Nandy 2012). Floristic inventories in sal forests vary dramatically in plot size, sampled area, and measurement threshold of minimum stem diameter, imposing a restriction in comparison of species richness (Table 5).…”
Section: Floristics and Species Richnessmentioning
confidence: 99%
“…Previous studies have reported 215 species of trees from seven forest types of Darjeeling foothills , 134 species of trees in the dry and moist sal forests of northern West Bengal (Kushwaha & Nandy 2012), 87 species of trees in Mahananda Wildlife Sanctuary (Shankar 2001), 74 species of trees in tropical parts of Darjeeling hills (Moktan & Das 2014). In addition to studies solely focusing on estimation of tree species richness many Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Forests of Central and Eastern Himalaya are also rich in plant species diversity and endemism (Singh & Singh 1987;Shankar 2001;Behera et al 2002;Das & Ghosh 2011;Kandel et al 2016), at the same time these forests are under heavy anthropogenic disturbances posing a threat on the existence of many rare species in the forest communities (Pandit et al 2007;Bhuyan et al 2003;Kushwaha & Nandy 2012). Eastern Himalayan forests are highly diverse as compared to northwest Himalaya with approximately fivefold higher number of species (Purohit & Dhar 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Kale and Roy (2012), however, observed a good correlation between NPP and plant diversity in another Indian tropical dry deciduous forest site. In yet another study, Kushwaha and Nandy (2012) found a significant decrease in plant species diversity from moist to dry forests differing in rainfall, disturbance, and management practices.…”
Section: Overviewmentioning
confidence: 93%